2007
DOI: 10.3748/wjg.v13.i18.2581
|View full text |Cite
|
Sign up to set email alerts
|

H pylori iceAalleles are disease-specific virulence factors

Abstract: AIM:To characterize and compare genotype profiles of H pylori strains isolated from patients with chronic gastritis and duodenal ulcer in western part of Turkey. METHODS:A total of 46 patients [30 chronic gastritis (CG) and 16 duodenal ulcer (DU)] who had undergone endoscopy because of dyspeptic complaints were studied. The antral biopsy specimens were evaluated for the presence of H pylori by rapid urease test and culture, and the genotype profiles were determined by real-time PCR. RESULTS:The cagA gene was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
17
3
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 32 publications
8
17
3
3
Order By: Relevance
“…In contrast to our results, a study done by Peek RM et al, showed an association between the allelic variant iceA1 and more severe inflammation of gastric mucosa [19]. Similar studies showing no association between iceA gene and peptic ulcer have been reported from Turkey and Lithuania [20,21]. We were unable to confirm an association between the iceA gene and clinical …”
Section: Detection Of Icea Gene In Gastric Specimen and In Their Corrcontrasting
confidence: 99%
“…In contrast to our results, a study done by Peek RM et al, showed an association between the allelic variant iceA1 and more severe inflammation of gastric mucosa [19]. Similar studies showing no association between iceA gene and peptic ulcer have been reported from Turkey and Lithuania [20,21]. We were unable to confirm an association between the iceA gene and clinical …”
Section: Detection Of Icea Gene In Gastric Specimen and In Their Corrcontrasting
confidence: 99%
“…In addition, the results of this study are consistent with previous reports (6,29) which no association was found between cagA gene and PU. However, some studies have been reported that cagA gene was statistically associated with PU (10,20,26).…”
Section: H Pylori Genotypessupporting
confidence: 93%
“…No s2m1 genotype was found in this study. This finding correlated confirm few data reported from other geographic regions of Turkey (6,10,18).…”
Section: H Pylori Genotypessupporting
confidence: 93%
See 2 more Smart Citations